Impact of Credit Risks on Profitability of the Systematically Important Licensed Commercial Banks in Sri Lanka - Mithila, G.; Kengatharan, L. (South Asian Journal of Finance, 2024)
Purpose: This paper focuses on analyzing the impact of credit risks on the profitability of six major licensed commercial banks in Sri Lanka which account for around 53% of the market share from 2017 to 2021. Design/Methodology/Approach: Return on Equity (ROE) was considered to measure the profitability while measuring the credit risks and it was carried out through Non- Performing Loan ratio (NPL), Capital Adequacy Ratio (CAL), Total Loan to Assets ratio (LTA), and Total Loan to Deposit ratio (LTD). STATA is used to analyze the data. To test the hypothesis, Pooled OLS, random, and fixed effect models are employed, and the most suitable model is picked through the Breusch and Pagan LM test and Hausman tests. Based on the results pooled OLS is selected for the interpretation with an Adjusted R2 of 74%. Findings: The study reveals a significant negative impact of NPL on profitability, suggesting that increased NPL proportions heighten credit risk, potentially leading to losses and reduced profitability. Conversely, the LTD shows a negative relationship, potentially exposing banks to higher default risks despite boosting interest income. However, LTA demonstrates a positive relationship with ROE within a certain limit, suggesting enhanced interest income without significant default risk escalation. CAR, however, does not directly impact profitability, emphasizing its role in ensuring capital adequacy and regulatory compliance. Originality: This study only focuses on the systematically important licensed commercial banks as they represent more than 50% of the market share and have a significant influence on the Sri Lankan economy. Hence, managing their credit risk exposures is significantly important for the country significantly important for the country.
Keywords: Credit Risk Management; Licensed Commercial Banks; Non-Performing Loans; Capital Adequacy Ratio; Loan to Asset Ratio; Loan to Deposit Ratio